THE ROLE OF THE VILLAGE HEAD AS A MEDIATOR IN RESOLVING LAND DISPUTES (CASE STUDY OF SIDOKUMPUL VILLAGE, KENDAL DISTRICT) - Kristianto Kristianto; Fitika Andraini (Sekolah Pascasarjana Universitas Swadaya Gunung Jati, 2023)
Indonesia is a country that adheres to a unitary form of government, but it is different if we look at the regional government system where Indonesia has adopted the principle of federalism as regional autonomy. Kendal Regency, geographically, some of its areas are mountainous areas, especially in the village of Sidokumpul, there are still requirements for customs in resolving land disputes. From this, Sidokumpul Village also implemented the ADR (Alternative Dispute Resolution) system. Disputes that occurred in village communities, especially Sidokumpul Village, in their settlement, the community preferred to use conflict resolution in a non-litigation way through the village head. This study uses normative juridical research, or also known as normative legalbresearchbmethod. Thebnormative juridicalbresearch methodbis library law researchbwhich is carriedbout by researching and studying literature materials or mere secondary data. The land dispute problems that occurred in Sidokumpul village during Ari Rimbawanto's 4 (four) years as Village Head could be resolved properly without having to to court, this is due to the crucial role of the village head in the settlement.